Crystal structure of the α-ketoglutarate-dependent non-heme iron oxygenase CmnC in capreomycin biosynthesis and its engineering to catalyze hydroxylation of the substrate enantiomer - Hsiao, Yu-Hsuan; Huang, Szu-Jo; Lin, En-Chi; Hsiao, Po-Yun; Toh, Shu-Ing; Chen, I-Hsuan; Xu, Zhengren; Lin, Yu-Pei; Liu, Hsueh-Ju; Chang, Chin-Yuan (Frontiers in Chemistry, 2022)
CmnC is an α-ketoglutarate (α-KG)-dependent non-heme iron oxygenase involved in the formation of the l-capreomycidine (l-Cap) moiety in capreomycin (CMN) biosynthesis. CmnC and its homologues, VioC in viomycin (VIO) biosynthesis and OrfP in streptothricin (STT) biosynthesis, catalyze hydroxylation of l-Arg to form β-hydroxy l-Arg (CmnC and VioC) or β,γ-dihydroxy l-Arg (OrfP). In this study, a combination of biochemical characterization and structural determination was performed to understand the substrate binding environment and substrate specificity of CmnC. Interestingly, despite having a high conservation of the substrate binding environment among CmnC, VioC, and OrfP, only OrfP can hydroxylate the substrate enantiomer d-Arg. Superposition of the structures of CmnC, VioC, and OrfP revealed a similar folds and overall structures. The active site residues of CmnC, VioC, and OrfP are almost conserved; however Leu136, Ser138, and Asp249 around the substrate binding pocket in CmnC are replaced by Gln, Gly, and Tyr in OrfP, respectively. These residues may play important roles for the substrate binding. The mutagenesis analysis revealed that the triple mutant CmnCL136Q,S138G,D249Y switches the substrate stereoselectivity from l-Arg to d-Arg with ∼6% relative activity. The crystal structure of CmnCL136Q,S138G,D249Y in complex with d-Arg revealed that the substrate loses partial interactions and adopts a different orientation in the binding site. This study provides insights into the enzyme engineering to α-KG non-heme iron oxygenases for adjustment to the substrate stereoselectivity and development of biocatalysts.